DESAIN PROPOSISI NILAI LAYANAN KONSULTASI USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) - Muhammad Eko Utomo; Astri Ghina (Universitas Galuh, 2023)
CV Joint Effect Transform is an IT company that initially developed web-based applications for company profiles, GIS for roads and bridges in various provinces in Indonesia. CV Joftra experienced a failure that required it to terminate its business in 2021 due to a business model that was still unclear and the difficulty of establishing a value map and customer profile. This problem makes it a challenge that encourages to find out more about the main problems both experienced by CV Joftra and prospective customers from CV Joftra. Currently CV Joint Effect Transform is trying to develop a mobile application for MSME business consulting. The purpose of this research is to identify the customer profile of CV Joftra, to find out the value map of CV Joftra and to create a match between the Value Map and the Customer Profile on CV Joftra. Data collection techniques in this study were carried out by means of in-depth interviews, observation, and secondary data collection.